2009
DOI: 10.18268/bsgm2009v61n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Geoquímica sedimentaria en áreas de pesca de arrastre y no arrastre de fondo en la costa de Sinaloa-Sonora, Golfo de California

Abstract: ResumenLos estudios geoquímicos y sedimentológicos realizados para evaluar el efecto de la pesca de arrastre de fondo en México, son práctica-mente inexistentes. En el presente trabajo se contrastan sitios de arrastre y no arrastre de la pesca del camarón en la costa de Sinaloa-Sonora. El análisis del tamaño de grano medio indicó diferencias estadísticamente significativas entre sitios de arrastre y no arrastre. Sorprendentemente, las variables geoquímicas (carbonato de calcio, carbono y nitrógeno orgánico, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…We did not collect sediment samples. However, Sánchez et al (2009) characterized the following three main sediment types from the study area: (i) core 1 -fine sand, located in the northern section of the study area; (ii) core 2 -loamy sand, distributed in the central part of the study area; and (iii) core 3 -silt-clay, confined to the southern study area. Goodwin & Pease (1991) described the spatial distribution of P. generosa in 6 areas from Puget Sound, Washington.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not collect sediment samples. However, Sánchez et al (2009) characterized the following three main sediment types from the study area: (i) core 1 -fine sand, located in the northern section of the study area; (ii) core 2 -loamy sand, distributed in the central part of the study area; and (iii) core 3 -silt-clay, confined to the southern study area. Goodwin & Pease (1991) described the spatial distribution of P. generosa in 6 areas from Puget Sound, Washington.…”
Section: Resultsmentioning
confidence: 99%
“…Mean surface temperature varies from 17.5°C in January to 32°C in August. The study area sediments are of 3 main types: (i) fine sand, located in the northern section of the study area; (ii) loamy sand, distributed in the central part of the study area; and (iii) silt-clay, confined to the southern study area (Sánchez et al 2009). It was restricted the fishing area to the 30 m isobath to assure diver safety, and because it is the maximum legal fishing depth (DOF 2012).…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%
“…Results similar to those of our study were found comparing sediment composition between trawled and unfished areas. For example, for prawn trawling in the coast of SinaloaeSonora (Mexico), the bottom structure and composition have been described as able to absorb the trawling effects (Sánchez et al, 2009). Also, no differences in particle size distribution and sediment types were found between fished and unfished experimental sites in blue mussel beds (Dolmer et al, 2001).…”
Section: Physical Disturbancementioning
confidence: 99%
“…En la actualidad se han descripto seis especies de Panopea, tres de las cuales habitan en el Hemisferio Sur: P. abbreviata (Valenciennes, 1839) se distribuye desde Río de Janeiro a Puerto Deseado, su valva mide unos 150 mm de longitud; P. zelandica (Quoy y Gaimand, 1835) habita en aguas poco profundas (5-25 m) de la Isla Stewart (Nueva Zelanda), en sustratos pelíticos y arenosos; mide entre 65 y 121 mm de longitud y puede extender su sifón hasta 45 cm sobre el sustrato; P. smithae Powell, 1950, también es endémica de Nueva Zelanda, tiene una conchilla de menor tamaño que P. zelandica (90-110 mm de longitud) y habita a mayor profundidad en sustratos gruesos y finos (Beu y Maxwell, 1990;Gribben, 2003). Estudios sobre ecología y reproducción de Panopea globosa (Dall 1898) han mostrado que se distribuye formando agregados y que su densidad poblacional está determinada biológicamente por su condición gonocórica y su hábito infaunal y ambientalmente por disponibilidad de nutrientes, turbidez, temperatura y principalmente por el tipo de sustrato, en este sentido se ha observado una mayor densidad de individuos en sustratos limo-arcillosos (Gómez-García, 2005;Sánchez et. al., 2009;Cortez-Lucero, 2013) y limo-arenosos (Godwin y Pease, 1991); esta diferencia de sustratos observada, se considera que puede estar determinada además por la presencia de otras especies.…”
Section: C4 C1unclassified